PHLPP1 regulates region-specific astroglial mitochondrial fission in response to oxidative stress in the male rat hippocampus - Ji-Eun Kim; Su Hyeon Wang; Tae-Cheon Kang (Scientific Reports)
Abstract Astrocytes have specialized functions depending on their localization. This region-dependent heterogeneity of astrocytes shows marked difference in astroglial responses to various stimuli. In the hippocampus, the populations of astrocytes in the stratum radiatum of the CA1 region (CA1 astrocytes) and the molecular layer of the dentate gyrus (DG astrocytes) have more complex structures than other regions. In the present study, we investigated whether oxidative stress induces distinct regulation of mitochondrial dynamics in CA1- and DG astrocytes, and which signaling pathways are relevant to these region-specific events in male rats. L-Buthionine sulfoximine (BSO)-induced oxidative stress led to mitochondrial fission in DG astrocytes concomitant with increased leucine-rich repeat protein phosphatase 1 (PHLPP1) expression and dynamin-related protein 1 (DRP1) S616 phosphorylation without altering AKT S473 and glycogen synthase kinase 3β (GSK3β) S9 phosphorylation, which were inhibited by PHLPP1 siRNA and SC79 (an AKT activator). BSO increased AKT S473 and GSK3β S9 phosphorylation in CA1 astrocytes without affecting their mitochondrial length or PHLPP1 expression, which was attenuated by 3-chloroacetyl-indole (an AKT inhibitor). These findings suggest that PHLPP1 may facilitate mitochondrial fragmentation in response to oxidative stress through the AKT-GSK3β-DRP1 pathway in DG astrocytes, but not in CA1 astrocytes, highlighting the region-specific heterogeneity in astrocytes.